Correlation of electrochromic properties and oxidation states in nanocrystalline tungsten trioxide1. Issue 24 (28th June 2015) - Darmawi, S.; Burkhardt, S.; Leichtweiss, T.; Weber, D. A.; Wenzel, S.; Janek, J.; Elm, M. T.; Klar, P. J.
<x xml:space="preserve">Abstract</x> In nanocrystalline tungsten trioxide, the main coloration change can be attributed to the formation of W4+.